PEMIKIRAN AKHLAK MENURUT SYAIKH UMAR BIN AHMAD BARADJA - Adim, Abd (Faculty of Ushuluddin and Humanities, 2016)
It is important to deepen Akhlak teachings through seeing a figure of Ulama, who has a high integrity between knowledge and akhlak. Syekh Umar Ahmad Baradja is an Ulama who has a good character and he was very productive to make a lot of wiritings. Some of them are seperti Al-Akhlaq Lil Banin, kitab Al-Akhlaq Lil Banat, kitab Sullam Fiqih, kitab 17 Jauharah, dan kitab Adâiyah Ramadhan. All of them were written in Arabic language, since 1950 were used as a main book in almost Islamic boarding school curriculumin Indonesia. He carved Indonesian SantriâsÂ character indirectly by his books. These books (Al-Akhlaq Lil Banin and kitab Al-Akhlaq Lil Banat) are as references for teachers in giving students external and internal education to control their attitude and behavior in daily life. Especially, when they are in public society and worship. The special things in his books are they made guidance about character (Akhlak) in two versions. One version is for boys and the other is for girls. The versions were made according to the needs of boys and girls to create a perfect character (Akhlak al-Karimah) to Allah and His creations. In the book also provided about some duâa (prayer text) and good actions, which had exemplified by Prophet Muhammad (pbuh) based on Qurâan and Sunnah. Syekh Umar Ahmad Baradja had told that before we come into mystical world or spiritual, we should learn about Akhlak teachings comprehensively. Likewise, who does good actions in this world, he will get matchless happiness. There is a harmony relationship between theservant and his God. It is the meaning of ethics in Sufism performance. We can take the model from the fabulous figure, who was able to relieve someoneâs thirst in his heart and gave a light to the way to Allah.Â